Isolation of Hv-CRKP with co-production of three carbapenemases (blaKPC, blaOXA-181 or OXA-232, and blaNDM-1) and a virulence plasmid: a study from a Chinese tertiary hospital - Li, Ping; Luo, Wan-ying; Xiang, Tian-Xin; Peng, Ting-xiu; Luo, Shuai; He, Zhi-yong; Liao, Wenjian; Wei, Dan-Dan; Liu, Peng; Wan, La-gen; Zhang, Wei; Liu, Yang (Frontiers in Microbiology, 2023)
Background: The worldwide dissemination of K. pneumoniae strains is a significant public health concern, as these organisms possess a unique capacity to acquire genetic elements encoding both resistance and hypervirulence. This study aims to investigate the epidemiological, resistance, and virulence characteristics of K. pneumoniae isolates that carry both virulence plasmids and blaOXA-48-like genes in a tertiary hospital in China. Methods: A total of 217 clinical isolates of carbapenem-resistant K. pneumoniae (CRKP) were collected between April 2020 and March 2022. The antimicrobial susceptibility test was conducted to evaluate the drug resistance profile. The molecular mechanisms were determined by PCR amplification. Clonal lineages were assigned using MLST and PFGE. The plasmid incompatibility groups were identified using PBRT. The transferability of carbapenemase-encoding plasmids and pLVPK-like virulence plasmids was assessed via conjugation. The plasmid location of rmpA2 was determined using S1-PFGE and southern blotting hybridization. The virulence potential of the strains was assessed using the string test, capsular serotyping, and a Galleria mellonella larval infection model. Results: Of the 217 CRKP clinical isolates collected, 23% were identified as carrying blaOXA-48-like genes. The main common OXA-48-like carbapenemase enzymes were found to be blaOXA-181 and blaOXA-232. MLST and PFGE fingerprinting analysis revealed clonal transmission and plasmid transmission. OXA-48-like producing CRKP isolates mainly clustered in K64 ST11 and K47 ST15 . PBRT showed that the blaOXA-181 and OXA-232 producing Hv-CRKP were mainly carried on ColE-type, IncF , and IncX3. Eight clinical strains of hv-CRKP were identified as carrying three carbapenem-resistant genes(blaKPC, blaOXA-181 or OXA-232, and blaNDM-1). All eight strains were hypervirulent and carrying a pLVPK-like virulent plasmid. Conclusion: In our investigation, we have observed the emergence of Hv-CRKP carrying blaOXA-48-like genes,which identified two genetic relationships: clonal transmission and plasmid transmission. PBRT analysis showed that these genes were mainly carried ColE-type, IncF, and IncX3 plasmids. These strains have been shown to be hypervirulent in vitro and in vivo. Additionally, eight clinical strains of CR-hvKP were identified as carrying three carbapenem-resistant genes(blaKPC, blaOXA-181 or OXA-232, and blaNDM-1). Hence, further investigation and active surveillance of hypervirulent OXA-48-like producing Hv-CRKP strains are necessary to prevent the dissemination of these perilous strains.